Three-dimensional reconstruction of electron micrographs reveals intrabulbar circuit differences between accessory and main olfactory bulbs - Moriya-Ito, Keiko; Endoh, Kentaroh; Fujiwara-Tsukamoto, Yoko; Ichikawa, Masumi (Frontiers in Neuroanatomy, 2013)
Three-dimensional (3D) reconstruction of synaptic arrangement on a particular dendrite provides essential information regarding neuronal properties and neural microcircuits. Unconventional synapses are particularly good candidates for such steric attribution. In main and accessory olfactory bulbs (MOBs and AOBs), there are dendrodendritic reciprocal synapses (RSs) between excitatory projection neurons and inhibitory interneurons. Although the fine structure and configuration of these synapses have been investigated in MOB, their characteristics in AOB were unknown. In this study, we performed 3D AOB reconstruction using serial section transmission electron microscopy. We found numerous RSs on primary dendrites from glomeruli to mitral/tufted (MT) cell somas. These synapses formed between dendritic shafts of MT cells and large dendritic spines, or so-called gemmules, of granule (Gr) cells. This indicates that chemical signals received by a glomerulus are regulated in the primary dendrite of an MT cell before reaching the AOB. In MOB, RSs are located on secondary dendrites and act as lateral and self-inhibiting following mitral cell depolarization. Our results indicate that AOB intrabulbar microcircuitry is quite different from that in the MOB.